CARDIOPROTECTIVE EFFECT OF PHYSICAL REHABILITATION IN PATIENTS WITH ISCHEMIC-ORIGIN DIASTOLIC DYSFUNCTION AFTER PERCUTANEOUS CORONARY INTERVENTION - N. P. Lyamina; A. N. Nosenko; I. B. Razborova; O. V. Orlikova; E. V. Kotel'nikova; E. S. Karpova (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study effect of long-term controlled physical training (CPT) of moderate intensity on diastolic function, depending on the degree of recanalization, in patients with ischemic heart disease (ICD) with left ventricle diastolic dysfunction (DD) who underwent percutaneous coronary intervention (PCI). Material and methods. Patients with ICD (n=60, all males, aged from 49 to 58 years) who had undergone PCI last 3–6 weeks were included into the study. They were randomized into two groups depending on CPT availability in the rehabilitation program. Standard clinical examination, diastolic function assessment, exercise tolerance test were performed at baseline, after 6 and 9 months. Results. The long-term CPT of moderate intensity led to diastolic function improvement in 15.6% of patients after 6 months and 28.1% - in 9 months. Improvement of diastolic function in ICD patients with complete recanalization was observed after 6 months of CPT moderate intensity. Longer period of physical rehabilitation (9 months or more) was required for patients with incomplete recanalization. The improvement of diastolic function without CPT was observed after 6 months in 2 (7.1%) patients with a relaxation type of DD and complete recanalization. Normalization of diastolic function without CPT after 9 months was observed in 10.7% of patients and 3.5% of patients showed DD progression. Conclusion. Inclusion of the long-term CPT of moderate intensity into the rehabilitation program has cardioprotective effect in ICD patients with ischemic DD undergoing PCI.